1979
DOI: 10.1042/bj1820577
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of glucose in hyper- and hypo-thyroid rats in vivo. Minor role of endogenous insulin in thyroid-dependent changes in glucose turnover

Abstract: 1. Rates and rate coefficients of glucose utilization and replacement (glucose turnover) as well as its recycling were determined in rats by using [U-14C]- and [2-3H]-, [3-3H]- or [6-3H]-glucose. 2. In euthyroid rats, the blood concentration of glucose was 1.5 times and its turnover rate was 2 times as high in the fed state as in the starved state; consequently the rate coefficient, a measure of the capacity of rats to utilize blood glucose, was also higher in the former than in the latter. 3. Induction of mil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0
1

Year Published

1981
1981
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 22 publications
1
12
0
1
Order By: Relevance
“…It was found that in non-diabetic rats the excess of thyroid hormones may increase blood insulin (7,16), suggesting that the observed drop in glycemia maybe caused by do direct action of thyroid hormones on glucose disposal and metabolism. Thyroid hormones given to diabetic rats could ameliorate intracellular transport of this sugar followed by its accelerated metabolism (18,33), in agreement with previous observations (19) demonstrating that thyroid hormones are capable of enhancing glucose turnover in animals with mild diabetes.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…It was found that in non-diabetic rats the excess of thyroid hormones may increase blood insulin (7,16), suggesting that the observed drop in glycemia maybe caused by do direct action of thyroid hormones on glucose disposal and metabolism. Thyroid hormones given to diabetic rats could ameliorate intracellular transport of this sugar followed by its accelerated metabolism (18,33), in agreement with previous observations (19) demonstrating that thyroid hormones are capable of enhancing glucose turnover in animals with mild diabetes.…”
Section: Discussionsupporting
confidence: 79%
“…It was also observed that thyroid hormones restrict some disturbances found in diabetes such as delay in fetal lung maturation (27) and diabetic cardiomyopathy (25). Moreover, thyroid hormones may partially ameliorate GLUT4 expression (33) and glucose utilisation (19) in animals with diabetes. Their beneficial influence on sorbitol accumulation in tissues of diabetic rats was also recently reported (28).…”
mentioning
confidence: 84%
“…By using a specific radioimmunoassay to measure intracellular concentrations of rabbit liver pyruvate kinase, Johnson and Veneziale (14) reported that, in general, hormonal control of the enzyme is through regulation of its catalytic state; however, their preliminary data for thyroxine treatment left open the possibility of induction of new, more active enzyme. Regulation by endogenous insulin activity is unlikely, even though insulin levels are elevated in mildly hyperthyroid rats (10,11) and insulin has been shown to increase pyruvate kinase activity in vivo (15) and to antagonize the inhibition of pyruvate kinase by glucagon in isolated hepatocytes (16). However, studies by Okajima and Ui (11) with streptozotocindiabetic rats and rats treated with antiserum against insulin show that the increased glucose turnover observed in hyperthyroid rats is largely independent ofendogenous insulin.…”
Section: Resultsmentioning
confidence: 95%
“…In general, the flux through pyruvate kinase is greatly decreased in hepatocytes from fasted, as compared with fed, rats (8), presumably because of elevated glucagon levels (9) and depressed insulin levels (10,11) in the fasted state. By using '4C tracer techniques, Rognstad (12) determined that the rate ofpyruvate kinase flux was nearly 50% ofthe rate ofgluconeogenesis from lactate in hepatocytes from T3-treated, fasted rats, which is similar to the ratio measured under the same conditions in hepatocytes from fed euthyroid rats (8).…”
Section: Resultsmentioning
confidence: 99%
“…It is obvious in the present study that the serum insulin and C-peptide levels after 2-h of post-glucose loading are lower than those at fasting state. To explain this status, Okajima and Michio (1978) stated that in hypthyroidism, alpha-adrenergic receptors are predominant over bet-actions which are responsible for pancreatic section of insulin from β-cells.…”
Section: Discussionmentioning
confidence: 98%